Limonene Extraction From Citrus Waste As An Eco-Friendly Solvent: Conventional And Non Conventional Techniques - A Review - Waskito, Andreas Gangsar Bayu; Armita Sari, Pande Made Nova (Universitas Pahlawan Tuanku Tambusai, 2025)
Limonene is a tepenoid compound found abundantly in orange peel waste that can be used as a green solvent due to its hydrophobic or nonpolar nature to reduce the use of chemical solvents that are harmful to the environment. This study aims to review factors that support the limonene extraction process such as extraction method, temperature, power, extraction time and also solvent ratio. This article is compiled based on literature obtained from Google Scholar and Pubmed using the keywords